A deep 3D residual CNN for false‐positive reduction in pulmonary nodule detection. Issue 5 (25th March 2018) - Jin, Hongsheng; Li, Zongyao; Tong, Ruofeng; Lin, Lanfen
Abstract : Purpose: The automatic detection of pulmonary nodules using CT scans improves the efficiency of lung cancer diagnosis, and false‐positive reduction plays a significant role in the detection. In this paper, we focus on the false‐positive reduction task and propose an effective method for this task. Methods: We construct a deep 3D residual CNN (convolution neural network) to reduce false‐positive nodules from candidate nodules. The proposed network is much deeper than the traditional 3D CNNs used in medical image processing. Specifically, in the network, we design a spatial pooling and cropping (SPC) layer to extract multilevel contextual information of CT data. Moreover, we employ an online hard sample selection strategy in the training process to make the network better fit hard samples (e.g., nodules with irregular shapes). Results: Our method is evaluated on 888 CT scans from the dataset of the LUNA16 Challenge. The free‐response receiver operating characteristic (FROC) curve shows that the proposed method achieves a high detection performance. Conclusions: Our experiments confirm that our method is robust and that the SPC layer helps increase the prediction accuracy. Additionally, the proposed method can easily be extended to other 3D object detection tasks in medical image processing.